2014
DOI: 10.1111/1365-2745.12232
|View full text |Cite
|
Sign up to set email alerts
|

Testing predictions of the Janzen–Connell hypothesis: a meta‐analysis of experimental evidence for distance‐ and density‐dependent seed and seedling survival

Abstract: The Janzen–Connell hypothesis proposes that specialist natural enemies, such as herbivores and pathogens, maintain diversity in plant communities by reducing survival rates of conspecific seeds and seedlings located close to reproductive adults or in areas of high conspecific density. Variation in the strength of distance- and density-dependent effects is hypothesized to explain variation in plant species richness along climatic gradients, with effects predicted to be stronger in the tropics than the temperate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
634
12
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 541 publications
(689 citation statements)
references
References 63 publications
35
634
12
8
Order By: Relevance
“…This is further supported by the fact that the proportion of neighbors that were conspecific declined significantly with focal tree size at all sites, particularly for sapling-sized neighbors. Numerous studies have reported strong conspecific negative density-dependent mortality in both tropical and temperate forests (Augspurger 1984, Terborgh et al 2008, Uriarte et al 2004a, Stoll and Newbery 2005, Chen et al 2010, Swamy and Terborgh 2010, Bai et al 2012, Comita et al 2014), particularly at early life stages (e.g., seedling and sapling stages; Zhu et al 2015). Our results are consistent with these other studies and demonstrate that such density-dependent mortality patterns are strong enough to structure forest composition.…”
Section: Effect Of Conspecific Neighbors On Local Compositionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is further supported by the fact that the proportion of neighbors that were conspecific declined significantly with focal tree size at all sites, particularly for sapling-sized neighbors. Numerous studies have reported strong conspecific negative density-dependent mortality in both tropical and temperate forests (Augspurger 1984, Terborgh et al 2008, Uriarte et al 2004a, Stoll and Newbery 2005, Chen et al 2010, Swamy and Terborgh 2010, Bai et al 2012, Comita et al 2014), particularly at early life stages (e.g., seedling and sapling stages; Zhu et al 2015). Our results are consistent with these other studies and demonstrate that such density-dependent mortality patterns are strong enough to structure forest composition.…”
Section: Effect Of Conspecific Neighbors On Local Compositionsupporting
confidence: 91%
“…Our results are consistent with these other studies and demonstrate that such density-dependent mortality patterns are strong enough to structure forest composition. Negative interactions with conspecific neighbors can result from strong intraspecific competition for resources, but a large body of literature points to distance/density-responsive, host-specific natural enemies (e.g., pathogens, insect herbivores) as the underlying mechanism, consistent with the Janzen-Connell hypothesis (e.g., Janzen 1970, Connell 1971, Mangan et al 2010, Bagchi et al 2014, Comita et al 2014.…”
Section: Effect Of Conspecific Neighbors On Local Compositionmentioning
confidence: 76%
“…However, a recent meta‐analysis by Comita et al. (2014), which addressed distance‐ and density‐driven Janzen–Connell effects based on a larger number of studies, supports the general validity of both distance‐ and density‐driven Janzen–Connell effects across different biomes and habitats. One prominent cause of Janzen–Connell effects is the predation of seeds by granivorous animals.…”
Section: Introductionmentioning
confidence: 62%
“…2014). Although some studies examined postdispersal seed predation in temperate experimental and semi‐natural grassland systems, they focused on the effects of plant species richness (Pufal and Klein 2013; Preukschas et al.…”
Section: Introductionmentioning
confidence: 99%
“…In natural forest ecosystems, native species coexistence is maintained by native seedling recruitment limitation assuming that host specific parasites (e.g., pathogens and herbivores) are more likely to damage conspecific seeds and seedlings the closer they germinate to the parent tree (distance-dependent coexistence mechanism explained by the Janzen and Connell Hypothesis (Connell 1971;Janzen 1970)). Biogeographic studies have supported the parent tree distance-dependent mechanism to explain species coexistence across latitudinal gradients from boreal to temperate systems and across different ecological guilds (Comita et al 2014). However, it is still unknown if distance-dependent mechanisms in regard to recruitment limitation apply to closed-canopy urban forest ecosystems invaded by exotic invasive plant species (hereafter invasive species).…”
Section: Introductionmentioning
confidence: 99%